Educational Reform in the Sultanate of Oman towards Achieving Qualitative Internal Efficiency of Basic Education Cycle 2 System - al-Hajri, Salim Mohammed Amur (2010)
The main issue of this study was on the educational reform and how it was leading towards efficiency particularly internal efficiency of the Omani education system. Much has been done by so many people and a lot of money has been spent to reform the system over last forty years. These inputs of educational reform (finance, activities and time) have accumulated over time to serve the present system. However, the question was whether accumulated inputs contributed towards the effectiveness and efficiency of the system. The main objectives of this study were to examine the educational reform in Oman with a view towards identifying internal efficiency of the Basic Education Cycle 2 in the Sultanate of Oman.